Ultrasonic duplex scanning as the standard for diagnostics of periphery arterial diseases of lower limbs in patients with diabetes mellitus in the development of purulent-necrotic complications. - Shapoval, S. D.; Savon, I. L.; Ryazanov, D. Yu.; Maksimova, O. O.; Slobodchenko, L. Yu. (Medicni Perspektivi, 2018)
Diabetic foot or the syndrome of diabetic foot (SDF) is the problem due to a high frequency of ablations of the lower extremities followed with a significant social, psychological and economic consequences. The research objective is to estimate diagnostic opportunities of ultrasound doppler scanning (UDS) of arteries of lower extremities in the patients with diabetes mellitus (DM) in development of purulent-necrotic complications. The main group consisted of 141 patients with DM who were treated at purulent-septic center «City Hospital N 3» in Zaporizhzhya, during 2017-2018. Control group – 274 patients who were receiving treatment during 2009-2013. The average duration of DM was 12,8±2,9 years. Average age of patients was 56,3±5,3 years. 63 (44,7%) were men, women – 78 (53,3%). The groups were representative by key indicators and the accompanying pathology. During hospitalization patients had signs of purulent-necrotic lesion of the lower extremity. The complex of diagnostic actions included obligatory diagnostics of a vascular bed of the lower extremities by means of UDS. By comparison with retrospective data it was defined that the number of DM patients with vascular problems in development of purulent-necrotic complications has increased. If earlier the percentage of distribution to etiological forms made up: neuropathic - 36,9%, ischemic - 23,4%, mixed – 39,7%, currently, mixed form (p<0,05) is noted in larger percent of patients – 51%.UDS is the best screening of vascular pathology in patients with DM in development of purulent-necrotic complications by means of which it is possible to find hemodynamically significant or critical stenosis of vessels and in due time to offer the patient one of blood supply restoration options.